Desenvolvimento de eletrodos modificados com Poli-1-aminonaftaleno e Poli-1,5-diaminonaftaleno e aplicação na determinação de analitos de interesse farmacêutico - Silva, Quésia Guedes da (2010)
The aim of this work was to study the electrochemical response of the electrode modified with poly-1-aminonaphthalene (1-PAN) and poly-1 ,5- diaminonaphthalene (1,5-PDAN) for dopamine (DA), noradrenaline (NA) adrenaline (AD) and hydroquinone (HDQ) determination in pharmaceutical preparations by means cyclic voltammetry and differential pulse (DPV). The films of a 1-PAN and 1,5- PDAN were electropolymerized on the platinum electrode by cyclic voltammetry. The surface of the films of a 1-PAN and 1,5-PDAN was characterized by SEM technique. The best results were obtained for DA with electrodes prepared in solutions with 1- aminonaphthalene and 1,5-diaminonaphthalene 0.01 mol L-1 in the perchloric acid 1.0 mol L-1, and 70 cycles. The electrode of 1-PAN showed voltammetric response only after the cathodic pre-treatment of -0.7 V for 3 s, and for the electrode of 1.5- PDAN this pretreatment resulted in better definition of peak and higher density current. The first procedure developed was determination to the DA using the electrodes of a 1-PAN and 1,5-PDAN by technique DPV, the analytical curve was linear in the dopamine concentration ranges of 9.90 and 122 μmol L-1, with a detection limit of 4.22 μmol L-1 and 19.6 and 99.0 μmol L-1 with a detection limit of 4.25 μmol L-1, respectively. Further, we studied the determination of NA using electrodes of 1-PAN and 1,5-PDAN by technique DPV, presenting a linear response between 9.90 and 82.5 μmol L-1, with a detection limit of 0.85 μmol L-1 and 9.90 and 90.9 μmol L-1 with a detection limit of 1.81 μmol L-1, respectively. For determination of AD employing electrodes of 1-PAN and 1,5-PDAN by technique DPV, the calibration curve was linear over the concentration range between 29.1 and 145 μmol L-1, with a detection limit of 8.35 μmol L-1 and 38.4 and 166 μmol L-1 with a detection limit of 15.8 μmol L-1, respectively. Finally, a procedure for the determination of HDQ using the electrode of 1,5-PDAN by technique DPV was developed. The analytical curve was linear in the HDQ concentration range between 74.0 and 690 μmol L-1, with a detection limit of 24.1 μmol L-1.These results were concordants with the comparative method, the spectrophotometric, with an acceptable relative error, which suggests the applicability of electrochemical methods proposed in samples of pharmaceutical formulations.